Stohastički, dezagregatni model ponašanja korisnika ceste - Radović, Blagota (Promet - Traffic&Transportation, 2012)
This paper deals with calibration (structuring) of a stochastic disaggregate binary model of road use selection: the motorway of a parallel road option. The variables of the model are the length of the road used and differences in the time of journey on the motorway and parallel road. Considering the road user/Es manner of assessment of time savings, a time variable has been structured in two ways: in the shape of ’differences’ (time of journey on the motorway- time of journey on the parallel road) i. e. the quotient (time of journey on the motorway /time of journey on the parallel road).